Study, design and development of a new add-on function for the FRICTORQ® - Friction Test Instrument - Silva, Luís F. (2012)
The assessment of handle properties is of utmost importance in materials in our everyday life. There is a wide range of materials there are used in contact with the human skin, which may cause several unpleasant skin reactions. The FRICTORQ® is a laboratory equipment developed by the authors to measure the friction coefficient in fabrics, to enable a quantitative assessment of touch/handle, in order to predict the comfort behaviour of 2D/3D structures when used or touched by humans. In a further development, the FRICTORQ® was redesigned to accommodate a new testing kit function to determine the friction coefficient of fabrics in a liquid environment. This new design will be explained and the results obtained while testing different swimwear fabrics and hospital garments will be also presented and discussed.